Improving Scheduling Efficiency: A Mathematical Approach to Multi-Operation Optimization in MSMEs - Reyner Pérez-Campdesuñer; Alexander Sánchez-Rodríguez; Margarita De Miguel-Guzmán; Gelmar García-Vidal; Rodobaldo Martínez-Vivar (Mathematics)
Optimizing the use of resources is a key aspect of organizational management. Various methods have been developed and applied to optimize different variables, including sequencing methods that aim to minimize work time. This paper presents an integrated approach for optimizing the sequencing of operations, considering indicators such as usage time, completion time, waiting time, delivery delay, and flow time. A multi-criteria optimization method with weighted aggregation was used, employing either an exhaustive search or a heuristic algorithm with nested loops, in which multiple possible combinations of operational sequences were evaluated, considering several key indicators and their respective weights. The application of the methodology in a press validated its effectiveness, providing managers with key information to prioritize the indicators according to their needs, whether optimizing resource usage or minimizing waiting times and delays. The application resulted in a 95.3% improvement in the level of utilization; a 79.3% reduction in the average completion time; a 90.5% reduction in machine waiting time; and a 90.9% decrease in product delivery delay. The results show that prioritizing the objective function leads to a balanced optimization of all indicators, improving operational efficiency and reducing flow time. This study contributes to the body of knowledge on production scheduling by offering a novel multi-criteria optimization approach in manufacturing settings. The validated methodology can be adapted to a variety of industries and offers flexibility to align with the specific interests of each organization.